C7‐Indole Amidations and Alkenylations by Ruthenium(II) Catalysis. Issue 30 (29th June 2020) - Choi, Isaac; Messinis, Antonis M.; Ackermann, Lutz
Abstract: C7−H‐functionalized indoles are ubiquitous structural units of biological and pharmaceutical compounds for numerous antiviral agents against SARS‐CoV or HIV‐1. Thus, achieving site‐selective functionalizations of the C7−H position of indoles, while discriminating among other bonds, is in high demand. Herein, we disclose site‐selective C7−H activations of indoles by ruthenium(II) biscarboxylate catalysis under mild conditions. Base‐assisted internal electrophilic‐type substitution C−H ruthenation by weak O‐coordination enabled the C7−H functionalization of indoles and offered a broad scope, including C−N and C−C bond formation. The versatile ruthenium‐catalyzed C7−H activations were characterized by gram‐scale syntheses and the traceless removal of the directing group, thus providing easy access to pharmaceutically relevant scaffolds. Detailed mechanistic studies through spectroscopic and spectrometric analyses shed light on the unique nature of the robust ruthenium catalysis for the functionalization of the C7−H position of indoles. Abstract : Lucky seven : The challenging C7−H activation of indoles has been accomplished by ruthenium(II) catalysis. The versatile ruthenium catalysis allowed C−N andC−C bond formation, scalable reactions, and the traceless removal of the directing group. Detailed mechanistic investigations based on diverse analysis tools shed light on a novel mode of action.